The polynomial p(x) is, p(x)= x3-5x2-8x+48.Use the Factor Theorem to show that (x + 3)is a factor of p(X)

First of all it is using the factor theorem. 

so need to use that to show it is a factor 

We do this by P of (-3) should = 0 

So substitute x with -3 

 p(-3)= (-3)3 - 5 (-3)2- (-3)8 + 48

= 0 

-27-45+24+48=0 

Answered by Mehr-Un-Nisa B. Maths tutor

4803 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

given y = x^2 - 7x + 5, find dy/dx from first principles


Differentiate (x^2)cos(3x) with respect to x


Make x the subject of the equation: 5x+1 = 2-4x


How do I find the equation of the normal to the curve y=x^2 at the point (x1,y1)? Where x1=2 and y1=4 .


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences